Sosial Media Marketing Sebagai Moderasi Pengaruh Content dan Event Terhadap Customer Engagement - Farida Akbarina; Eva Fathussyaadah; Shohib Muslim; Muhammad Hery Santosa; Abdul Razak Munir (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Social media has become an important platform in building and maintaining customer engagement. So social media is the most effective way to increase customer engagement towards products or services. In this study, this study uses quantitative research. This study aims to determine social media marketing as a moderation of the influence of content and events on customer engagement. This study focuses on e-commerce customers, by applying the Non-Probability Sampling technique to determine the sample. And the population obtained in this study was 200 respondents. The analysis technique in this study used Smart PLS. The results of this study found that content and events have an effect on customer engagement. Social media as a moderating variable is able to moderate the influence of content and events on customer engagement.